Causation, Fault, and Fairness in the Criminal Law - Skolnik, Terry (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2019)
Over the past two decades, the Supreme Court of Canada has developed an overarching account of causation rooted in the need to prevent the conviction of the morally innocent. Despite these valuable contributions, there are certain limitations to the way causation is currently conceptualized in Canadian criminal law. This article aims to address those limitations and offer a plausible alternative account of causation and its underlying rationale. It advances three core arguments. First, it explains why judges should employ one uniform formulation of the factual causation standard: significant contributing cause. Second, it offers a new account of legal causation that distinguishes foreseeability as part of the actus reus from foreseeability inherent to mens rea. In doing so, it sets out why legal causation is primarily concerned with fairly ascribing ambits of risk to individuals. Third, it refutes the Supreme Court of Canada’s underlying justification for the causation requirement. Contrary to the Court’s invocation of the importance of moral innocence, this article demonstrates that causation principles actually tend to concede the accused’s moral fault while still providing reasons for withholding blame for a given consequence. This reveals that causation’s underlying rationale is more closely related to concerns about fair attribution rather than moral innocence. Ultimately, this article reframes causation to better answer one of the most basic questions in the criminal law: Why am I being blamed for this?